Dandelion fire - Wilson, Nathan D. (New York : Yearling, 2009)
As Henry York's time on his aunt and uncle's farm draws to a close, Henry makes a rash decision to step into one of the alternate universes hidden behind the cupboard doors and search for the truth about who his parents are and where he came from.
Wilson's Children, July 2009
School Library Journal, January 2009
Horn Book, October 2009
Kirkus Review, January 2009
4.7
3-6
Keywords: Magic -- Juvenile fiction; Space and time -- Juvenile fiction; Doors -- Juvenile fiction; Families -- Kansas -- Juvenile fiction; Cousins -- Juvenile fiction; Kansas -- Juvenile fiction; Magic -- Fiction; Space and time -- Fiction; Doors -- Fiction; Family life -- Kansas -- Fiction; Cousins -- Fiction; Kansas -- Fiction; Magic -- Fiction; Space and time -- Fiction; Doors -- Fiction; Family life -- Kansas -- Fiction; Cousins -- Fiction; Kansas -- Fiction